A modified three terms PRP conjugate gradient method - Songhua WANG; Yong LI; Jiaqi WU; Naichang LU (Journal of Hebei University of Science and Technology, 2018)
In order to effectively solve a class of large-scale unconstrained optimization problems and overcome the shortcomings of other algorithms, such as complex algorithms, large memory and computer programming difficulties, a new search direction is defined, which is based on some traditional three terms PRP conjugate gradient methods as well as combined with the research results of three terms conjugate gradient and some new line searches in recent years. A new line search algorithm is used to construct the algorithm, which proves that it has the properties of automatic full descent and trust region, and proves its global convergence under appropriate conditions. Numerical experiments has showed that the new algorithm is more competitive than the traditional three-term PRP conjugate gradient method in solving a class of large-scale unconstrained optimization problems. The new algorithm with better convergence property provides a more efficient algorithm basis for solving a class of large-scale unconstrained optimization problems.